Avaliação da Supramolecularidade de complexos triazenidos mononucleares e binucleares de Ag(I) - Fank, Juliana de Oliveira (2009)
This work presents the synthesis and the investigation of the crystalline and molecular structure of five new mononuclear or binuclear complexes of Ag(I) with monocatenated triazenido ligands. The mononuclear complexes were synthesized from the binucleares complexes. With the addition stoichiometric of the ligand triphenylphosphine occurs the split of the binuclear complex, removing the ligand triazenido of the function bridge between the two atoms of silver, forming the complex mononuclear the silver chelate by ligand triazenide. Were evaluated in relation the occurrence of intermolecular interactions though secondary non-covalent bonding and non-classic hydrogen bonds. The research was based on X-ray diffraction to analyse structurally the formation of supramolecular arrangements performed by complexes in the solid state, that could show in supramolecular arrangents unidimensional, bidimensional and tridimensional. The complexes 5 [Ag(C6H4FNNNC6H4NO2)]2, 6 [Ag(C6H4ClNNNC6H4NO2)]2, 7 [Ag(C6H4NO2NNNC6H4NO2)P(C6H5)3], 8 [Ag(C6H4ClNNNC6H4NO2)P(C6H5)3] and 9 [Ag(C6H4BrNNNC6H4NO2)P(C6H5)3] present non-covalent secondary bonding Ag-ç2- arene ð resultant from the interaction ç2-arene with ð character of a phenyl ring substituted into ortho position and an Ag atom. Besides these non-covalent bonding the complexes 5, 7, 8 and 9 form supramolecular arrangements through the nonclassic hydrogen bonding C-H O.